Project of the new gravimetric network and test survey in Slovenia - KOLER, Božo; MEDVED, Klemen; KUHAR, Miran (Contributions to Geophysics and Geodesy, 2021)
Based on analyses of old gravimetric surveys carried out in the territory of the Republic of Slovenia a project of the new gravimetric network was developed. The geological assessment of suitability of the preserved and new planned gravimetric stations was completed. Additionally, in the territory of Slovenia test gravimetric surveys with the relative gravity meter Scintrex CG-3M No. 10341 were performed. Test measurements were tied to the absolute gravimetric stations. The main aims of the test measurements included testing, trial operation of the instrument and acquisition of experience in measuring the first order gravimetric network. The measuring campaign was performed at the stations where gravity was previously measured. All readings were evaluated and a comparison with the previous gravity values in the surveyed stations was performed.